Security Prices in a Competitive Market: More about Risk and Return from Common Stocks. - Downes, David H.; Brealey, Richard A. (Journal of Finance, 1972)
This book is a sequel to An Introduction to Risk and Return from Common Stocks (The MIT Press, 1969), although it is fully self-contained and can be read independently. Both books describe in non-technical language the behavior of common stock prices as revealed by formal statistical work. In the process they offer a broad survey of recent quantitative academic research on the subject, much of which is currently in an inaccessible form.The earlier book, which the New York Times says rates high as reading for every professional investor, was concerned with the basic factors affecting risk and return from common stocks. The present work is concerned primarily with unusual factors that may influence the value of an investment. It is divided into three parts: the first considers various company decisions that may affect the price of its stock (decisions on capital structure, dividend policy, and acquisitions); the second looks at particular types of activity in the stock (insider trading, short selling, and secondary distributions); while the third considers securities that are convertible to common stock.Richard Brealey continues to cover new ground. Little of the material in this book can be found in existing investments texts, and like his first book, it should provide an invaluable source of information for the professional investor and may well be received in the same spirit.